Recent Young Adult Sports Literature in Review - LISA A. HAZLETT; ANN MARIE SMITH; ANITA DUBROC (University of Oklahoma Libraries, 2020)
Readers eager to learn more about contemporary works of sports-related YAL will look forward to Lisa A. Hazlett's review of Gut Check (Kester, 2019), Ann Marie Smith's review of Heroine (McGinnis, 2019), and Anita Dubroc's review of Here to Stay (Farizan, 2018).